2016
DOI: 10.22436/jnsa.009.11.15
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point theorems for generalized multivalued nonlinear F -contractions

Abstract: In this paper, we introduce certain new concepts of α-η-lower semi-continuous and α-η-upper semicontinuous mappings. By using these concepts, we prove some fixed point results for generalized multivalued nonlinear F-contractions in metric spaces and ordered metric spaces. As an application of our results we deduce Suzuki-Wardowski type fixed point results and fixed point results for orbitally lower semi-continuous mappings in complete metric spaces. Our results generalize and extend many recent fixed point the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…0 such that for all x, y ∈ X , ðÞ , then T has a fixed point in X . For more in this direction, see, [28][29][30][31]. Here, we give the concept of multivalued α-F-weak-contractions and prove some fixed point results.…”
Section: Some Fixed Point Resultsmentioning
confidence: 95%
“…0 such that for all x, y ∈ X , ðÞ , then T has a fixed point in X . For more in this direction, see, [28][29][30][31]. Here, we give the concept of multivalued α-F-weak-contractions and prove some fixed point results.…”
Section: Some Fixed Point Resultsmentioning
confidence: 95%
“…To fulfill our purpose we use the recent technique, which was given by Wardowski [37]. For the sake of completeness, we will discuss the basic lines [23,24,25].…”
Section: Definition 23 ([27]mentioning
confidence: 99%
“…Recently, some authors demonstrated the Wardowski original conclusions without the criteria ( 2 ) and ( 3 ) in various ways (see, [6,7]). For more in this direction, see [8][9][10][11][12][13][14][15]. Very recently, Derouiche and Ramoul [16] introduced the notions of extended -contractions of the Suzuki-Hardy-Rogers type, extended -contractions of the Hardy-Rogers type, and generalized -weak contractions of the Hardy-Rogers type as well as establishing some new fixed-point results for such kinds of mappings in the setting of complete b-metric spaces.…”
Section: Introductionmentioning
confidence: 99%